Effect of pH and Temperature on Fructosyltransferase (Ftase) Production from Candida Krusei - Mohd Nazarni, Che Isa (2013)
The relationship between consumer, food and health become one of important issues because of increasingly demand on healthier food. Based on functional properties of fructosyltransferases (FOS), the consumer demands have been increasing in order to response on that. In Malaysia, it is reported that the number of diabetic patients is increasing daily and it is one of the fatal diseases. A significant driving force in the ‘functional food’ market place is the quest by consumers to optimize their health through food. The enzyme source synthesis production can be divided into two classes which are from microorganism and plant. Where by plant, the production is restricted from any sources .In view of that, production of crude enzyme from micro fungi is studied in order to obtain high yield of FOS. This study is carried out using sucrose as a substrate in the fermentation process to produce crude enzyme from micro fungi, namely Candida krusei. In this study, an investigation on pH and temperature of enzyme was analysing ranging from 3.0-8.0 and 25-55oC, respectively. The crude enzyme was analysed using UV-Vis U-1800 Spectrophotometer at wavelength of 540 nm. The protein concentration was determined using UV-Vis U-1800 Spectrophotometer at wavelength of 750 nm. By using an extracellular enzyme which is fructosyltansferase (FTase) from selected micro fungi, the food-grade FOS can be produced commercially from sucrose. As result indicates that the highest pH and temperature for activity of FTase from Candida krusei is pH5.5 and temperature 55oC. The highest enzyme activity (148.501 IU/mL) was figured out at pH 5.5, 55oC and the specific activity was observes as 10.638 IU/mg. As a conclusion, this research was done to produce other alternative way of producing crude FTase using selected microfungi that are less harmfull to use in a production of FOS in food health industries.